Three-dimensional evaluation of periodontal effects after surgically assisted rapid maxillary expansion (Research, Society and Development, 2022)
Objective: To evaluate the periodontal effects of maxillary teeth in patients who underwent surgically assisted rapid maxillary expansion (SARME) and compare the results with the amount of expansion and the surgical technique performed.  Material and Methods: Cone-beam computed tomography (CBCT) of nineteen patients who underwent SARME were selected, preoperative (up to one month before surgery) and postoperative (six to eight months after surgery) to analyze measurements of bone thickness, alveolar bone level alveolar segment tilting, and tooth tipping. An analysis of all medical records was also performed, regarding the amount of expansion achieved, and surgical technique performed. The patients were divided in groups with and without pterigomaxillary disjunction. Results: Tooth upper first premolar and first molar on the left side, and second premolar and first molar on the right side all presented bone loss in the period after surgery. All teeth, with exception of first molars in both sides of the maxillae, presented dental tipping. And, it was also found that the greater the amount of expansion, the greater will be the bone loss in level and thickness (BL, ABT5). And, that the greater the angulation of the tooth, the greater the bone level loss. Conclusions: In conclusion, after surgery and the use of the Hyrax device, the buccal alveolar bone thickness suffered statically significant losses, also, some teeth suffered segment tilting and tooth tipping. The present study also found greater bone loss in patients who suffered a greater amount of expansion.